2017
DOI: 10.1097/qad.0000000000001595
|View full text |Cite
|
Sign up to set email alerts
|

Blood neuron-derived exosomes as biomarkers of cognitive impairment in HIV

Abstract: Objective To investigate proteins associated with neuronal damage in plasma neuron-derived exosomes (NDE) of HIV-infected subjects as a liquid biomarker for cognitive impairment. Methods Plasma NDE were isolated using precipitation and immunoadsorption with antibody to a cell surface specific neuronal marker. Total exosomes and NDE were enumerated, characterized and proteins extracted and targets quantified by ELISA. Results Plasma NDE from 23 HIV seropositive individuals of which 11 had mild cognitive imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
90
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 107 publications
(102 citation statements)
references
References 54 publications
(56 reference statements)
5
90
1
Order By: Relevance
“…Firstly, it is important to note that flotillins are universally expressed by all cell types, and consist as a component of all subtypes of extracellular vesicles, independently to their density or size [61]. In addition, it has been indicated that the concentration of plasma neuron-derived exosomes was lower in neurocognitively impaired individuals (regardless of the cause) in comparison with controls [60]. Furthermore, flotillin-1 has been reported to be enriched in exosomes from CSF samples obtained from patients at early stage of severe traumatic brain injury, although no comparisons with control subjects were made in this study [62].…”
Section: Discussion and Future Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…Firstly, it is important to note that flotillins are universally expressed by all cell types, and consist as a component of all subtypes of extracellular vesicles, independently to their density or size [61]. In addition, it has been indicated that the concentration of plasma neuron-derived exosomes was lower in neurocognitively impaired individuals (regardless of the cause) in comparison with controls [60]. Furthermore, flotillin-1 has been reported to be enriched in exosomes from CSF samples obtained from patients at early stage of severe traumatic brain injury, although no comparisons with control subjects were made in this study [62].…”
Section: Discussion and Future Perspectivesmentioning
confidence: 99%
“…Furthermore, flotillin levels have been found to be negatively correlated with amyloid burden, as shown by the mean cortical PiB retention levels in PiB-PET [10]. However, flotillin-2 levels were shown elevated in brain sections of older non-demented humans compared with younger individuals [41], as well as levels of plasma neuron-derived exosomes were lower in aged HIV-infected individuals compared with controls [60], raising concerns regarding the efficacy of flotillin levels to effectively discriminate between AD and normal ageing. In this regard, flotillin levels were found to remain stable with advancing age in healthy controls in the abovementioned study [10], highlighting the possibility that their levels may not be affected by ageing process itself.…”
Section: Flotillin As a Novel Biomarker Candidate For Ad: Clinical Evmentioning
confidence: 99%
“…Dr. Bond’s group recently described a procedure, also using iodixanol velocity gradients, for the effective isolation and separation of exosomes from HIV-1 virions in human plasma (Konadu et al 2016). Dr. Pulliam’s group successfully isolated neuron-derived exosomes from plasma of HIV-infected subjects using precipitation and immunoadsorption with an antibody to a neuronal specific cell surface marker (Sun et al 2017). Additionally, Dr. Hill’s group reported a novel method for the successful enrichment of exosomes from human brain tissue (Vella et al 2017).…”
Section: Resultsmentioning
confidence: 99%
“…More recently, exciting studies have also highlighted alterations in plasma neuron-derived EVs (NDEs) during HIV infection (Sun et al 2017). Intriguingly, in this study, the authors demonstrated that NDEs were influenced by both HIV infection as well as neurocognitive impairment, as evidenced by increased expression of stress proteins such as HMGB1, neurofilament-1, and amyloid beta protein in the NDEs compared with plasma exosomes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation